2006
DOI: 10.1016/j.commatsci.2006.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Design of acoustic trim based on geometric modeling and flow simulation for non-woven

Abstract: In order to optimize the acoustic properties of a stacked fiber nonwoven, the microstructure of the non-woven is modeled by a macroscopically homogeneous random system of straight cylinders (tubes). That is, the fibers are modeled by a spatially stationary random system of lines (Poisson line process), dilated by a sphere. Pressing the non-woven causes anisotropy. In our model, this anisotropy is described by a one parametric distribution of the direction of the fibers. In the present application, the anisotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
118
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(123 citation statements)
references
References 16 publications
2
118
0
Order By: Relevance
“…Using spherical coordinates, β characterizes the directional distribution of fibers. The density of the directional distribution is given by Equation (1), (Schladitz et al, 2006) The density is thus independent of φ, i.e. the density exhibits rotational symmetry with respect to the z-axis.…”
Section: Random Generation Of 3d Structuresmentioning
confidence: 99%
“…Using spherical coordinates, β characterizes the directional distribution of fibers. The density of the directional distribution is given by Equation (1), (Schladitz et al, 2006) The density is thus independent of φ, i.e. the density exhibits rotational symmetry with respect to the z-axis.…”
Section: Random Generation Of 3d Structuresmentioning
confidence: 99%
“…The idea of representing fiber based material by randomly distributed cylinders was presented by Tomadakis and Sotirchos already in 1993 [48]. A commonly used stochastic model for fiber based GDLs was presented by Schladitz et al [49]. In this model straight fibers of non-woven GDLs are generated by a 3D dilated Poisson line process.…”
Section: Introductionmentioning
confidence: 99%
“…First, Hao and Cheng created their virtual geometry from the Schladitz model [49] whereas our approach is based on the model from Thiedmann [51] and its extension regarding the binder [52,53].…”
Section: Introductionmentioning
confidence: 99%
“…The reconstructed fibrous medium is used as a basis for the computation of its geometrical, transport, and sound absorbing properties. In discussing a range of experimental data on the microstructure of non-woven fibrous materials involving x-ray micro computed tomography and microscopy analysis, previous works had relied on ad hoc "fiber anisotropies" 7,8 or "volume weighted average radius." 9 Here it is shown that, in conjunction with the bulk porosity, these parameters: (1) Contribute to a precise description of the acoustical characteristics of fibrous absorbents.…”
Section: Introductionmentioning
confidence: 99%